ANALISIS METODE PERMAINAN DALAM PEMBELAJARAN BAHASA ARAB KELAS 7 SMP 9 MUHAMMADIYAH BOARDING SCHOOL TANGGULANGIN - Rahmadhani, Gurit; Ammar, Farikh Marzuki (Jurnal Dedikasi Pendidikan, 2025)
This study aims to examine the application of the game method in Arabic language learning for grade 7 of SMP 9 Muhammadiyah Boarding School Tanggulangin. The approach used in this study is qualitative, with the research subjects being grade 7 Putra of SMP 9 Muhammadiyah Boarding School Tanggulangin. Then for the data analysis technique used in this study is "Miles & Huberman" including data reduction, data presentation, and drawing conclusions. Source triangulation was carried out by comparing the results of observations, interviews, and field notes. The results of the study indicate that the application of the game method can encourage significant improvements in students' learning skills. They demonstrate clearer, more structured speaking skills, and pay active attention. In addition, they are also able to interact and collaborate well, use appropriate language according to context, and manage verbal and nonverbal expressions effectively. Overall, this study shows that the game method is an effective way to develop students' values in learning. Therefore, it is recommended to use the game method in between Arabic language learning times